Analisis Penerapan Pajak Penghasilan Pasal 23 di Sekretariat Wakil Presiden Periode Tahun 2023 - Zuhdii, Pradhitya Afrizkyaldi; Armeliza, Diah; Zairin, Gentiga Muhammad (Jurnal Akuntansi, Perpajakan dan Auditing, 2025)
The study examines the application of Income Tax Article (ITA) 23 at the Secretariat of the Vice President during 2023, focusing on the challenges faced such as difficulties in identifying services subject to ITA 23, transactions with partners lacking NPWP, and tax underpayment. Conducted through a qualitative approach with a descriptive analysis method involving interviews, literature review, and tax document analysis, the research found overall compliance with regulations, particularly PMK No. 141/PMK.03/2015, despite obstacles in tax withholding and reporting. The study aims to benefit the Secretariat by enhancing the tax administration system's structure and efficiency and could serve as a reference for other government agencies to bolster compliance and comprehension of tax regulations.